Factors Affecting Healthcare Employee Satisfaction and Their Relationship to Patient Satisfaction in Community Health Centres - Mustamu, Alva Cherry (Scripta Medica, 2024)
Background/Aim: In the realm of healthcare services, the satisfaction of medical professionals in their workplace environment has become a central concern closely associated with the perceived satisfaction levels of patients. This research investigated the intricate relationship between employee satisfaction and patient satisfaction within the context of community health centres. The study aimed to identify specific factors of employee satisfaction, such as compensation, supervision and work environment, that potentially influence the level of patient satisfaction. Methods: Employing a cross-sectional descriptive design, a total of 162 employees and 276 patients from 13 community health centres participated in this study, conducted between June and September 2023. The participants were selected based on specific criteria, including age above 17, fluency in Indonesian and ability to complete the questionnaires. The study utilised two questionnaires: one measuring patient satisfaction with aspects of healthcare service and the other gauging employee satisfaction concerning management practices in community health centres. Both questionnaires employed Likert scale measurements to gather responses. Results: The findings indicated a significant influence of investigated factors on patient satisfaction. Notably, compensation of employees emerged as a crucial factor significantly affecting patients satisfaction, aligning with previous research emphasising its importance in healthcare settings. Conversely, other factors such as supervision, work relationships, nature of work, opportunities for status change and work interactions with colleagues of employees did not exhibit a significant impact on patient satisfaction. Conclusions: The study findings conformed the importance of compensation as a pivotal factor in designing strategies to improve patient satisfaction in community health centres. While other factors like supervision and work interactions did not demonstrate statistically significant correlations, this suggests the potential for more complex relationships that warrant further investigation. Identifying specific factors that influence patient satisfaction in community health centres can significantly contribute to enhancing healthcare service quality and overall patient satisfaction in the future.